Developing Mathematics Assessment Instrument for Children with Autism Spectrum Disorder - Oom Sitti Homdijah; Euis Heryati; Ehan Ehan (Department of Special Education, 2021)
Academic assessment instruments are necessary for obtaining data about student learning needs. Teachers need assessment instruments to collect accurate information as a reference in devising learning programs. The development of mathematics assessment instrument for children with autistic spectrum needs to be carried out to produce valid and easy-to-use instrument for teachers to assess their students' mathematical abilities. This research results showed that the developed instrument consisting of four aspects, including numbers, counting operations, place-values, and fractions. The validity check revealed that this instrument could be considered as valid and usable.